Mary On Horseback - Wells, Rosemary (New York : Viking, 1998)
Summary: Tells the stories of three families who were helped by the work of Mary Breckenridge, the first nurse to go to the Appalachian mountains and give medical care to the isolated inhabitants.
Keywords: Breckinridge, Mary -- Biography; Frontier Nursing Service; Appalachian Mountains